2021
DOI: 10.21037/apm-20-2134
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in serum IL-6, IL-8, and IL-10 predict the outcome of ICU patients with severe COVID-19

Abstract: Background: Biomarkers to prognosticate the outcomes and guide the treatment of patients with severe coronavirus disease 2019 (COVID-19) are currently required. We aimed to investigate whether the dynamic variation of cytokines was associated with the survival of patients admitted to the intensive care unit (ICU).Methods: A retrospective study was performed on 40 patients with COVID-19 admitted to the ICU in Wuhan, China. Demographic, clinical, and laboratory variables were collected, and serum cytokines were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 29 publications
6
58
0
Order By: Relevance
“…Several reports show in particular that high serum levels of not only of the pro-inflammatory IL-6, IL-1b and TNFa but also anti-inflammatory cytokine IL-10 are associated with the severity of the disease and a higher comorbidity index among adults with COVID-19 (38,39,(41)(42)(43)(44)(45)(46)57). Changes in serum IL-6 and IL-10 levels act as a predictive biomarker to determining severe patient COVID-19 (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports show in particular that high serum levels of not only of the pro-inflammatory IL-6, IL-1b and TNFa but also anti-inflammatory cytokine IL-10 are associated with the severity of the disease and a higher comorbidity index among adults with COVID-19 (38,39,(41)(42)(43)(44)(45)(46)57). Changes in serum IL-6 and IL-10 levels act as a predictive biomarker to determining severe patient COVID-19 (44).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-10 are found to predict disease severity ( 38 ). Elevated serum levels of IL-6, IL-10, and tumor necrosis factor alpha (TNFα) in non-survivors have been detected, compared to those in the survivors ( 44 ). Also, a fatal outcome has been observed in patients with severe COVID-19 with kinetic variations in IL-6, IL-8, and IL-10, independently of sex, age, absolute lymphocyte count, direct bilirubin, hypertension, and chronic obstructive pulmonary disease ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients who were admitted to the ICU were also found to have higher plasma levels of IL-2, IL-7, IL-10, GCSF, IP-10, MCP-1, MIP-1α, and TNF-α than non-ICU patients [113]. Interestingly, while many of these cytokines and chemokines were also elevated in SARS and MERS patients, several studies have reported an increase in Th2-related anti-inflammatory cytokines IL-4 and IL-10 [115] in COVID-19 patients [113,[116][117][118][119][120], ascribing a seemingly unique cytokine profile to COVID-19. Even more interesting is that IL-10 levels were increased in severe COVID-19 patients, compared to the mild patients [113,[116][117][118][119][120].…”
Section: Cytokine and Chemokine Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…Interestingly, while many of these cytokines and chemokines were also elevated in SARS and MERS patients, several studies have reported an increase in Th2-related anti-inflammatory cytokines IL-4 and IL-10 [115] in COVID-19 patients [113,[116][117][118][119][120], ascribing a seemingly unique cytokine profile to COVID-19. Even more interesting is that IL-10 levels were increased in severe COVID-19 patients, compared to the mild patients [113,[116][117][118][119][120]. The induction of overlapping cytokines in SARS-CoV, MERS-CoV, and SARS-CoV-2 infections suggests a possible common immunopathogenic pathway induced by these highly pathogenic hCoVs.…”
Section: Cytokine and Chemokine Response To Sars-cov-2 Infectionmentioning
confidence: 99%